Design and evaluate a web-based Hanyu Pinyin instruction for non native Mandarin learners / Ong Sheau Fen, Chang Koo Tap and Lim Soo Giap - Ong, Sheau Fen; Chang, Koo Tap; Lim, Soo Giap (2008)
The Internet and the World Wide Web (WWW) continue to exert tremendous influence on our everyday lives. The use of the WWW as an instructional tool is gaining momentum as more teachers, instructors, and trainers incorporate it into their repertoire. Hanyu Pinyin (Romanised Mandarin) is used in the teaching and learning of Mandarin as a third language in UiTM. As the time allocated for teaching Hanyu Pinyin is insufficient for learners many of whom are exposed to Mandarin for the first time to satisfactorily comprehend the intricacies of its sound system, therefore it is necessary to devise some self-learning materials for learners to enable them to control and monitor their learning process in the absence of facilitator. In order to create a conducive self learning environment for learning Hanyu Pinyin, a web-based instruction was incorporated into the curriculum. Eventually, the effectiveness of the instruction was evaluated. The web- based Hanyu Pinyin instruction was constructed and evaluated on the basis of Instructional System Design methodology. Finally, this research discusses some limitations and constraints that were discovered and proposes some recommendations to overcome the limitations for the future research.